The study of the possibility of processing semi solid alloy AZ91D by the shell investment casting process [compact disc] - 212531 Norfazilah Mohd. Idris (Skudai : Universiti Teknologi Malaysia, 2006)
Project paper (Sarjana Muda Kejuruteraan (Mekanikal - Pembuatan)) - Universiti Teknologi Malaysia, 2006